A cell-penetrating artificial metalloenzyme regulates a gene switch in a designer mammalian cell - Yasunori Okamoto (Nature Portfolio, 2018)
Artificial enzymes can be used to elicit reactions in cells. Here, the authors developed such an artificial catalyst combined with a genetic switch, and showed that it was readily taken up by human cells and able to kick off a reaction cascade resulting in the biosynthesis of the desired product.